Principal component analysis of soil properties in assessing erodibility indices in the Northern Brahmaputra plains of Assam - DEKA, BIPUL; DUTTA, MARAMI (Journal of Soil and Water Conservation, 2020)
Fifty soils representing six different landscape units of the Northern Brahmaputra plains of Assam were collected for evaluating their erosional status. After estimating the soil physico-chemical and fertility related properties, various erodibility indices like clay ratio, silt/clay ratio, modified clay ratio, dispersion ratio, erosion ratio and erosion index were computed based on the measured soil data. Principal component analysis was carried out using 29 characters which included 23 soil properties and 6 erodibility indices. The principal factor analysis synthesized five factors explaining 80.38 per cent variability. The first factor which accounted for 51.79 per cent of the total variability was strongly influenced by erodibility indices and a set of related physico-chemical and fertility parameters. Based on the calculated factor scores it was found that the soils of the old flood plain are the most stable landscape unit of the studied area while, the structural hill soils are the most erodible one. The ranking of the soils appeared to be in close agreement with soil analytical and computed data.